Effects of acetone cyanohydrin, a derivative of cassava, on motor activity and kidney and liver function in Wistar rats - Rivadeneyra-Domínguez, E; J Rosas-Jarquín, C; Vázquez-Luna, A; Díaz-Sobac, R; Rodríguez-Landa, J F (Neurologia (Barcelona, Spain), 2019)
Acetone cyanohydrin (ACH) is a toxic substance present in cassava roots (Manihot esculenta Crantz) which results from enzymatic hydrolysis of linamarin. Long-term consumption is associated with 2 neurological disorders: konzo and tropical ataxic neuropathy. Previous studies have evaluated behavioural alterations linked to ACH consumption, but the toxic effects of this substance on physiological processes remain unknown. 32 male Wistar rats were assigned to 4 experimental groups (n=8 per group): a vehicle group (0.3mL saline solution, IP) and 3 ACH groups (PubChem CID: 6406) dosed at 10, 15, and 20mM/24h for 28 days. We evaluated spontaneous motor activity with the open field test and motor coordination with the rotarod and forced swimming tests at 0, 7, 14, 21, and 28 days of treatment. At the end of the assessment period (day 28), blood samples were collected by transcardiac puncture to evaluate kidney and liver function. ACH caused alterations in locomotor activity and promoted both lateral swimming and spinning in the forced swimming test at 21 and 28 days of treatment. Furthermore, it led to an increase in the levels of the parameters of kidney and liver function in a concentration-dependent manner, except for glucose and total bilirubin. Our results suggest that long-term consumption of this toxic compound present in cassava roots may be potentially dangerous for vulnerable subjects.